Electrical and thermal properties of SiC-Zr2CN composites sintered with Y2O3-Sc2O3 additives. Issue 2 (February 2017) - Jang, Seung Hoon; Kim, Young-Wook; Kim, Kwang Joo
Abstract: SiC-Zr2 CN composites were fabricated from β-SiC and ZrN powders with 2 vol% equimolar Y2 O3 -Sc2 O3 additives via conventional hot pressing at 2000 °C for 3 h in a nitrogen atmosphere. The electrical and thermal properties of the SiC-Zr2 CN composites were investigated as a function of initial ZrN content. Relative densities above 98% were obtained for all samples. The electrical conductivity of Zr2 CN composites increased continuously from 3.8 × 10 3 (Ωm) −1 to 2.3 × 10 5 (Ωm) −1 with increasing ZrN content from 0 to 35 vol%. In contrast, the thermal conductivity of the composites decreased from 200 W/mK to 81 W/mK with increasing ZrN content from 0 to 35 vol%. Typical electrical and thermal conductivity values of the SiC-Zr2 CN composites fabricated from a SiC-10 vol% ZrN mixture were 2.6 × 10 4 (Ωm) −1 and 168 W/m K, respectively.